Compliance with the National Health Insurance Fund in Tanzania: Could Out-of-Pocket be a Better Option? - Mtei, Gemini; Mushi, Deograsias (Tanzania Journal for Population studies and Development, 2009)
This study analyzes the National Health Insurance Fund (NHIF) in Tanzania with the objective of determining the level of compliance with this scheme, and the factors that would determine such compliance. Primary data from primary school teachers in Kilimanjaro and Dar es Salaam regions were collected through a questionnaire that required respondents and their households to give the history of their health status, and their valuation of NHIF. The results show that compliance with NHIF is correlated with age, sex, marital status, and location of the residence of the members. Other factors that have been found significant in determining compliance of the members include presence of an old aged dependant, use of public health facility, number of sick household members, occupation status, availability of drugs when using NHIF, and the type of disease episode befalling the household. A majority of members still prefer out-of-pocket compared to NHIF, though the former seems be expensive and not poor friendly. The study proposes a balance between the provision side of health care and the membership to NHIF as the latter has influence on compliance.